2010
DOI: 10.1111/j.1365-246x.2010.04764.x
|View full text |Cite
|
Sign up to set email alerts
|

An hp-adaptive discontinuous Galerkin finite-element method for 3-D elastic wave modelling

Abstract: International audienceWe present a discontinuous Galerkin finite-element method (DG-FEM) formulation with Convolutional Perfectly Matched Layer (CPML) absorbing boundary condition for 3-D elastic seismic wave modelling. This method makes use of unstructured tetrahedral meshes locally refined according to the medium properties (h-adaptivity), and of approximation orders that can change from one element to another according to an adequate criterion (p-adaptivity). These two features allow us to significantly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 64 publications
1
100
0
Order By: Relevance
“…Khors-Sansorny, et al, 2007) with a 10 m spatial discretization (i.e., more than 70 numerical cells per minimum wavelength; Bohlen and Saenger, 2006). Verification tests of our finite-difference method including topography were done by Maufroy (2010) through quantitative comparisons with the discontinuous Galerkin method introduced by Etienne et al (2010). The tests revealed solution discrepancies smaller than 25% for frequencies below 4 Hz in most of the studied area (see fig.…”
Section: Ground-motion Synthetic Databasementioning
confidence: 99%
“…Khors-Sansorny, et al, 2007) with a 10 m spatial discretization (i.e., more than 70 numerical cells per minimum wavelength; Bohlen and Saenger, 2006). Verification tests of our finite-difference method including topography were done by Maufroy (2010) through quantitative comparisons with the discontinuous Galerkin method introduced by Etienne et al (2010). The tests revealed solution discrepancies smaller than 25% for frequencies below 4 Hz in most of the studied area (see fig.…”
Section: Ground-motion Synthetic Databasementioning
confidence: 99%
“…However, there is no mathematical proof for unstructured meshes that guarantees numerical stability. (Hammer & Stroud, 1958) and explicit forms of these matrices could be found in Etienne et al (2010) for P 0 , P 1 and P 2 orders.…”
Section: Spatial Discretisationmentioning
confidence: 99%
“…These authors proposed the application of an additional damping in the PML, onto the directions parallel to the layer, leading to a multiaxial PML (M-PML) which does not follow strictly the matching property of PML in the continuum and which has a less efficient absorption power. Through various numerical tests, Etienne et al (2010) has shown that instabilities could be delayed outside the time window of simulation when considering extended M-PML from CPML. Table 2 gives the computation times for updating the velocity and stress wavefields in one element for one time step, for different approximation orders, without or with the update of the CPML memory variables (i.e.…”
Section: Absorbing Boundary Conditionmentioning
confidence: 99%
“…For example, the finite-element method [8,30,35] can approximate complex geometries and topographies by discretizing the models using triangular or tetrahedral cells. Other similar methods, for example, the discontinuous Galerkin [6,7,11,15,21], the finite-volume method [10,57,59], and the boundaryelement method [31,32], can also provide a measure of flexibility towards rugged interfaces by employing irregular grids. However, compared with finite-difference methods, these alternatives are almost always more computationally expensive and generally more complicated to implement.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the heterogeneity of the Earth, the simulation of seismic wavefields is achieved most commonly using numerical methods, such as the finite-element method [8,30,35], the finite-difference method [1,25,44,45], spectral-element method [23,24], or discontinuous Galerkin [6,7,11,15,21]. The most widely used is the finitedifference method, which uses finite differences to calculate the partial derivatives of wave equations numerically.…”
Section: Introductionmentioning
confidence: 99%